Acoustophoresis Enables the Label‐Free Separation of Functionally Different Subsets of Cultured Bone Marrow Stromal Cells. Issue 5 (29th June 2020) - Olm, Franziska; Lim, Hooi Ching; Schallmoser, Katharina; Strunk, Dirk; Laurell, Thomas; Scheding, Stefan
Abstract: Culture‐expanded mesenchymal stromal cells (MSCs) are promising candidates for clinical cell‐based therapies. MSC products are heterogeneous and we therefore investigated whether acoustophoresis, an ultrasound‐based separation technology, could be used for the label‐free enrichment of functionally different MSC populations. Acoustophoresis uses an ultrasonic standing wave field in a microchannel that differentially affects the movement of cells depending on their acoustophysical properties, such as size, density, and compressibility. Human bone marrow (BM) MSCs were generated by standard adherent culture in xeno‐free medium and separated by microchip acoustophoresis. MSCs with up to 20% higher proliferation and 1.7‐fold increased clonogenic potential were enriched in the side outlet of the chip compared to the input sample. These cells were significantly smaller (average diameter 14.5 ± 0.4 μm) compared to the center outlet fraction (average diameter 17.1 ± 0.6 μm) and expressed higher levels of genes related to proliferation and stem cell properties ( i.e ., Ki‐67 [1.9‐fold], Nanog1 [6.65‐fold], Oct4 [2.9‐fold], and CXCL12 [1.8‐fold], n  = 3) in the side outlet compared to input. Fractions of MSCs in G0 /G1 cell cycle phase were significantly enriched in the side fraction and an up to 2.8‐fold increase of cells in S/G2 /M phases were observed in center fractions compared to side fractions and 1.3‐fold increased compared to the input sample. Acoustophoresis did not compromise MSC phenotype, proliferation, clonogenic capacity, and viability (generally 87–98%), nor did it affect differentiation or immunomodulatory capacities. These results demonstrate that label‐free acoustic separation can enrich functionally different MSC subsets which can potentially be employed to produce better‐defined stromal cell products from cultured MSCs. Hence, acoustophoresis is a potentially promising separation technology to provide improved cell products for research and possible future clinical use. © 2020 The Authors. Cytometry Part A published by Wiley Periodicals LLC. on behalf of International Society for Advancement of Cytometry. Abstract : Culture‐derived mesenchymal stromal cell (MSC) products are morphologically and functionally heterogeneous. We demonstrate herein that label‐free acoustophoresis can effectively enrich smaller‐sized MSC subpopulations with high proliferation and clonogenic potential as well as higher expression of stem cell‐ and proliferation‐related genes, while preserving viability, differentiation capability, and immunomodulatory functions. Thus, acoustophoresis provides a gentle, label‐free tool to enrich different MSC subpopulations based on functional properties, which can potentially be employed to identify and produce better‐defined stromal cell products.